Application of quantitative approach focused on the competition of lactic acid bacteria culture with coagulase-positive staphylococci under the conditions related to artisanal cheese fermentation - Ľubomír Valík; Alžbeta Medveďová; Denisa Liptáková (Czech Journal of Food Sciences, 2011)
A quantitative analysis of Staphylococcus aureus growth was carried out in milk fermented with the mesophilic mixed-strain culture of lactic acid bacteria (LAB), in relation to the conditions prevailing during artisanal ewes' lump cheese production. Both the temperature and initial volume of the culture had a dramatic effect on the behaviour of the S. aureus strain under study. Depending on the conditions, the growth, reaching maximal population density (Nmax) and a strong inhibition of S. aureus were observed. Regression analysis of the results enabled us to explain the relationships between the parameters such as the growth or inhibition rate, lag phase and Nmax-N0 and the temperature and initial culture density on the other hand. The surface methodology enabled to show that the rate of S. aureus inhibition (rinh) was affected by the temperature and volume of LAB inoculum following the equation: rinh =-0.1302 + 0.02325 × T - 0.000975 × T 2 - 0.00001 × T 2 × V 02 (R = 0.965). The fact that S. aureus increased in number mostly only by about 1 log and did not reach 106 CFU/ml during our model experiments was the most useful for good manufacturing practice. The knowledge obtained in this study concerned with the quantitative behaviour of S. aureus including the information on the inhibition at the selected environmental factors (temperature, inoculum size, and pH) is essential for the improvement of the fermentation process, quality and safety of artisanal ewes' cheese production used as a raw material for industrial Bryndza cheese production.